Treason in the blood H. St. John Philby, Kim Philby and the spy case of the century - Brown, Anthony Cave 1929-2006 (Houghton Mifflin, 1994)
Kim Philby has been called "one of the most remarkable double-agents to have been exposed in our time." Harry St. John Bridger Philby, Kim Philby's father and mentor, was one of the most intriguing intellectuals and adventurers of our time, a manipulator who played a key role in establishing the modern Middle East. In this dual biography, Anthony Cave Brown, tells the extraordinary story of two men whose lives were directly opposed to the establishment into which they were born and for which they were bred. St. John, the brilliant Arabist, became a Moslem and political adviser to King Ibn Saud. He was the middleman in the U.S. acquisition of the Saudi oil concession, called by the State Department "the greatest commercial prize in the history of the planet." And as St. John turned to Mecca, Kim turned to the Kremlin, serving as a secret agent against the Anglo-American intelligence services for fifty-three years.
Keywords: Philby, H. St. J. B <1885-1960> -- (Harry St. John Bridger); Philby, Kim <1912-1988>; Philby, Harry St. J. B. -- 1885-1960; Philby, Kim -- 1912-1988; Spionage; Espionage, Soviet -- Great Britain; Spies -- Great Britain -- Biography; Großbritannien; Biografie